2007
DOI: 10.1111/j.1944-8287.2007.tb00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Division, Segmentation, and Interpellation: The Embodied Labors of Migrant Workers in a Greater London Hotel

Abstract: In this article, we explore the ways in which a divided and segmented migrant labor force is assembled to serve guests in a London hotel. We draw on previous studies of hotel work, as well as on cultural analyses of the ways in which employers and managers use stereotypical assumptions about the embodied attributes of workers to name workers as suitable for particular types of labor. We argue that a dual process of interpellation operates within service‐sector workplaces that is reinforced and resisted in dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
215
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(231 citation statements)
references
References 70 publications
5
215
0
4
Order By: Relevance
“…As several studies have demonstrated, limited language skills force migrant workers into roles that reinforce immobility and offer fewer opportunities to interact with 1 1 customers or other nationals, which might help to develop their language skills (see Adler & Adler, 1999;McDowell, 2009;Ryan et al, 2008). In the tourism sector, research on migrants' involvement in networks has largely concentrated on accessing employment (Devine, Baum, Hearns, & Devine, 2007a, 2007bMatthews & Ruhs, 2007McDowell, Batnitzky & Dyer, 2007. However, as we argue, networks within tourism employment are also a significant learning resource.…”
Section: Migrant Mobilities and Networkmentioning
confidence: 99%
“…As several studies have demonstrated, limited language skills force migrant workers into roles that reinforce immobility and offer fewer opportunities to interact with 1 1 customers or other nationals, which might help to develop their language skills (see Adler & Adler, 1999;McDowell, 2009;Ryan et al, 2008). In the tourism sector, research on migrants' involvement in networks has largely concentrated on accessing employment (Devine, Baum, Hearns, & Devine, 2007a, 2007bMatthews & Ruhs, 2007McDowell, Batnitzky & Dyer, 2007. However, as we argue, networks within tourism employment are also a significant learning resource.…”
Section: Migrant Mobilities and Networkmentioning
confidence: 99%
“…poor language skills), work below their actual qualifications have been reported to feel disadvantaged, devalued and deskilled in the UK (Currie, 2008). These sentiments -alongside the precarious positionality of some economic migrants -have been claimed to contribute to the development of less tolerant or racist attitudes towards difference (Cook et al, 2011a;McDowell, 2009;McDowell et al, 2007). While the arguably insecure or underprivileged position of some labour migrants might fuel negative perceptions of difference, it is crucial not to overlook the influence of other circumstances on the development of unfavourable attitudes towards the ethnic, national or religious Other.…”
Section: Migrant Encountersmentioning
confidence: 99%
“…It is important to note here that the majority of positions Irena and Piotr held after moving to the UK were low-skilled, including production-line work or cleaning, and frequently below their actual qualifications. Although labour migrant identities and attitudes are clearly differentiated by age, gender, skills, skin colour and class (McDowell, 2008), low-skilled migrants in the UK have been argued to use stereotypical assumptions about embodied attributes of their co-workers (McDowell et al, 2007). In the context of their precarious positions, feelings of being disadvantaged or devalued (e.g.…”
Section: Irena (Female Aged 50 Arrived To the Uk In 2008)mentioning
confidence: 99%
See 1 more Smart Citation
“…At one level, the answer is relatively simple for, as Hudson (2001, p.200) argues, the social divisions that people bring with them into the labour force are structurally and collectively created. There is evidence that the recruitment of migrant workers and distribution of jobs in hospitality are influenced by stereotyped views of employers based on factors such as gender, age, race and nationality (McDowell, et al, 2007, Anderson & Ruhs, 2008. However, for the small hotels in London this seems to be of secondary importance as more informal recruitment practices are in place: networks of family and friends, word of mouth and availability and readiness to accept the job appear to be important As the People 1 st report indicates, this only accounts for the recruitment of some managers.…”
Section: Migration and Migration Experience In A Mobile Sector Migranmentioning
confidence: 99%